Status Baku Mutu Air Laut untuk Kehidupan Biota dan Indeks Pencemaran Perairan di Pesisir Cirebon pada Musim Kemarau [Water Quality Standards for Marine Life and Pollution Index in Cirebon Coastal Area in the Dry Season] - Nasir Sudirman; Semeidi Husrin (Faculty of Fisheries and Marine Universitas Airlangga, 2014)
Abstract Coastal land that is adjacent to the sea are still is influenced by the tide. Cirebon coast generally have ramps and high turbidity due to sediment supply and waste from the river that empties into the sea. Cirebon coast is divided into two areas, namely governance City of cirebon and Regency of cirebon. Coastal conditions closely related to river, estuaries, and the ocean in the region, the changing nature of the river caused by human activities will affect the water quality and coastal environment. Environmental pollution occurs mainly in the fisherman areas and industry. Determination of contamination status was determined using the pollution index according to equation 1 Sumiotomo and Nerow (1970) in the Minister of the Environment decree No. 115 of 2003 on Guidelines for Determination of Water Quality Status. Criteria for determining the level of water quality based on water quality standards for marine life by the Minister of Environment Decree No. 51 of 2004. The methods of research is done by the measuring of pH, dissolved oxygen, conductivity, turbidity, temperature, salinity, organic matter using Water quality Cheker along the coast cirebon within 500m - 1Km from the beach in June as a representation of the dry season. The results of the analysis addressed that in the dry season there are 10stations lightly polluted, 6 stationsare being polluted and heavily polluted 4 station.